APPLICATION OF HSDPA TECHNOLOGY TO INCREASE THE SPEED AND RELIABILITY OF DATA TRANSMISSION IN COMMUNICATION NETWORKS - Дрововозов, В.; Бригинець, О. (Science-based technologies, 2010)
The technology of high speed downlink packet access HSDPA with the purpose of application to increase the speed and reliability of data transmission in modern communication networks is considered. Changes in network technology after the reorganization of the structure of the channel, input Fast Hybrid ARQ and Amplitude Modulation and Coding are analysed.